ANALISIS DOSIS PAPARAN RADIASI DARI PESAWAT PANORAMIK DI INSTALASI RADIOLOGI RUMAH SAKIT UMUM DAERAH RADEN MATTAHER JAMBI - Chintiya Romarti; Jesi Pebralia; Rista Mutia Anggraini (JOURNAL ONLINE OF PHYSICS, 2023)
This research aims to analyze the influence of distance and direction on radiation exposure values, assess the doses received by radiation workers and the general public, and evaluate the effectiveness of radiation protection from panoramic aircraft. The research method used is an experimental research method, where the researcher directly measures the variables of the study and conducts data analysis. The study was conducted by measuring radiation doses in various directions at distances ranging from 0.5 meters to 2.5 meters forward and to the right, and 0.5 meters to 1.5 meters to the left. Dose data reception was taken at operator room, service area, corridor, and waiting room points, and radiation protection effectiveness measurements were taken at corridor entrance, waiting room, and operator room points using a survey meter. The research results indicate that the radiation exposure dose is inversely proportional to the measured distance. The dose received by radiographers in the operator room is 0.107 μSv/hour, in the employee corridor, it is 0.0856 μSv/hour, and in the public waiting room, it is 0.0856 μSv/hour. The radiation protection effectiveness value in the operator room is 94.40%, at the patient entrance from the panoramic aircraft waiting room, it is 92.12%, and at the radiographer entrance from the employee corridor, it is 94.62%. According to the Tenth Value Thickness (TVT) concept, this is considered safe because the existing protection capabilities can effectively absorb radiation.